Akhlaq and Music: Student Character Development through Musical Expression - Ainusyamsi, Fadlil Yani (Asosiasi Mahasiswa Program Pascasarjana | Universitas Islam Darussalam (UID) | Islamic University of Darussalam | Ciamis | Jawa Barat, 2023)
The objective of this study is to ascertain endeavors aimed at cultivating students' character through the medium of music. This study employs qualitative methodologies, primarily focusing on conducting descriptive investigations. Data collecting involves utilising primary and secondary sources, encompassing theories, factual information, and documents pertaining to music, education, and character. Data analysis employs descriptive analysis, which involves the theoretical description of data through data collection, data reduction or simplification of theories and concepts, presentation of data by attempting to derive conclusions from various theories and concepts, and data verification, which entails rechecking the accuracy of the drawn conclusions and making necessary adjustments. The research findings indicate that music can contribute to attaining educational objectives, particularly in fostering the growth of an individual's personality and character in alignment with society's values and norms. The objective is to cultivate conscientious attitudes and conduct in individuals, positively contributing to society, nation, and state advancement.